2003
DOI: 10.1067/mtc.2003.90
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen as a chemotherapy adjuvant in the treatment of metastatic lung tumors in a rat model

Abstract: Hyperbaric oxygen enhanced the chemotherapeutic effect of doxorubicin both in cell culture and in the rat model. Aqueous oxygen infusion can be used to oxygenate mixed venous blood at levels similar to those obtained with the use of a hyperbaric chamber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…Within an oncological framework, we have demonstrated a relationship between liver regeneration and oxygen consumption. Improved liver regeneration with HBO therapy has been ascribed to an increase in the delivery of oxygen to the liver [49], and increased oxygen levels in liver tissue may give rise to an increase in the number of vessels and the mitotic rate in the tumor, thereby promoting the effectiveness of chemotherapy [47, 50].…”
Section: Discussionmentioning
confidence: 99%
“…Within an oncological framework, we have demonstrated a relationship between liver regeneration and oxygen consumption. Improved liver regeneration with HBO therapy has been ascribed to an increase in the delivery of oxygen to the liver [49], and increased oxygen levels in liver tissue may give rise to an increase in the number of vessels and the mitotic rate in the tumor, thereby promoting the effectiveness of chemotherapy [47, 50].…”
Section: Discussionmentioning
confidence: 99%
“…HBO 2 T enhances tumor-cell production of reactive oxygen species which contributes to the synergistic effects of HBO 2 T as an adjuvant treatment to standard care. Indeed, HBO 2 T enhances the efficacy of both radiation and chemotherapy in animal models [53], [54], [55], [56], [57].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, HBO has previously been used to enhance the pO 2 in hypoxic tumor tissue, to potentiate the effect of radio- and photo-therapy in both clinical and preclinical trials and also the effect of some forms of chemotherapy like doxorubicin, alkylating agents and 5FU [13-16]. This effect has been ascribed as increased cytotoxicity of the tumor cells to the chemotherapeutic drug in vitro [16,17] and enhanced neovascularisation in vivo [18]. However, recent studies have shown reduced vascularisation after HBO treatment in vivo [19-21].…”
Section: Introductionmentioning
confidence: 99%